Agroforestry education and professional level links in Peninsular Malaysia - Mohamed, Azmy; Ibrahim, Nor Izaida; Abd. Ghani, Awang Noor (Penerbit Universiti Malaysia Terengganu, 2013)
Past studies showed that agroforestry plays an important part in balancing and managing natural resources. However, agroforestry practices are not conspicuous in Malaysia, and most of the projects are also shat of success, and one of the main reasons being the lack of knowledge. A study was made to review the competency and education levels of officers working in agro based agencies and also to determine the links between the education and duties of these officers. This study was conducted with the purpose of identifying the perceptions of agroforestry education in Peninsular Malaysia, held by the officers at three level positions. The study was done in seven states in Peninsular Malaysia. A questionnaire was prepared based on a review of the literature and specific courses at various institutions. The questionnaire consisted of 16 items covering several agroforestry aspects of in which the technical competency of the officers was geared. One hundred and fifty-nine officers from agro based agencies participated in the study. Of those surveyed, 63.5% had never had agroforestry education while only 36.5% took a course in agroforestry in their education. The results showed that the level of agroforestry education was statistically significantly different for three group of officers (X2 (2, N=159) = 10.367, Ρ = .00) at .05 level of significance and that the proportion of variability in the ranked dependent variable accounted for by the status of agroforestry education was .256, indicating a moderate relationship between the group positions of the officers and the status of agroforestry education. The technical competence level of the officers in the agro based agencies in the multidisciplinary subjects was often weak. There was highly demand for intensified agroforestry training through regular in-services courses. Courses should include all categories of staff. Therefore, this study has raised awareness of the status of agroforestry at the professional level in agro based agencies.